External independent knowledge testing in Ukraine from a historical and social perspective - Pottroff, Viktoriya (Kansas State University, 2009)
This historical and qualitative inquiry investigates recent educational reform in Ukraine. On Tuesday, April 22, 2008 more than half a million Ukrainian high-school graduates were ordered to take an external assessment of student achievements. The new assessment model was named the External Independent Knowledge Testing and replaced the traditional forms of high school exit-entrance to higher educational institution exams in Ukraine. These changes in assessment strategies in the Ukrainian educational system illustrate the global trend of replacing diverse forms of national examinations with standardize multiple-choice assessments that can be scored by machines and could be viewed as a new page in the history of educational assessment. Educational assessment has become one of the most significant areas of research in the United States. It is not only a prominent issue in education today but also one of the most controversial issues in contemporary educational science. The debate is concentrated around the question of what purpose educational assessment serves. A growing body of international research suggests that educational assessment is a new mechanism of social and political control aimed to legitimize social inequalities. Thus, the primary goal of this study was to investigate what kind of changes the External Independent Knowledge Testing in Ukraine was expected to bring to Ukrainian society and whether the initial results of the reform were consistent with what was expected. Data was collected by means of interview, survey, and examining Ukrainian publications. The data revealed that the recent changes in traditional practices of assessment in Ukraine were aimed at serving much broader social purposes than those identified by Ukrainian policymakers. Under the guise of improving the quality of Ukrainian education and fighting corruption in higher education, the educational reforms in Ukraine are implementing an undetected new form of social and political preferences through education and testing. Thus, the reform helps new Ukrainian nobilities legitimize their status through the new system of exercising control over Ukrainian education.
Keywords: Education in Ukraine; Testing in Ukraine; Education, Tests and Measurements (0288)